Design And Construction Of Metal And Non-Metal Waste Selecting Tools Based On Arduino Uno - Mulianto, Moch Amin Fajar; Adi Winarno; Mohamad Ilham (Universitas PGRI Adi Buana Surabaya, 2024)
This Arduino-based automatic metal and non-metal waste sorting tool is designed to sort waste, making it easier to recycle waste. The main components of this tool include Arduino (as a tool control system), proximity sensor (as a metal scrap detector), servo motor (as a driver to isolate metal scrap) and LCD to display the type of metal scrap. In terms of waste sorting, the Proximity sensor will detect waste. If the waste is detected as metal waste, the servo motor will rotate to the right and direct the waste to a special metal waste bin. The LCD screen will display the type of metal waste. If the proximity sensor does not detect non-metal waste, the servo motor will rotate to the left and direct the non-metal waste to a special non-metal waste bin. This type of waste sorter is very helpful in reducing waste because it can be processed according to the type of waste.